Survey of global health education in physical medicine and rehabilitation residency programs across the United States - Marla Petriello, DO; Amy Mathews, MD; Kaile Eison, DO; Elana Hartman, MD; Hannah Steere, MD (The Journal of the International Society of Physical and Rehabilitation Medicine)
The need for global rehabilitation as well as the interest of medical trainees in global health education is rising. Physical medicine and rehabilitation (PM&R) physicians and trainees are trained to care for people with disabilities. Our objectives were to (1) quantify the interest, access, and type of global health education currently available for US PM&R residents and fellows, (2) determine the rehabilitation-specific topics, amount of time, and learning formats preferred by PM&R residents and fellows in developing a global health education course, and (3) determine the barriers to incorporating these global health experiences perceived by both trainees and program directors (PDs), as well as PD support for global health education for trainees. Two cross-sectional surveys created via REDCap software were administered to PM&R residents and fellows and to PDs. Responses from 96 residents and fellows (maximum N=1505) and 40 PDs (maximum N=105) were recorded. A total of 32.2% of trainees and 27.5% of PDs reported global health training was currently available in their program. Global health-specific didactic lectures (65.5%) were the most commonly reported global health experience available to trainees. In addition, the majority of trainees reported they were either “very likely” (27.0%) or “moderately likely” (34.8%) to apply for an elective global health curriculum, with the most interest noted in an elective rotation abroad (82.8%). Trainees (72.1%) and PDs (89.5%) both identified the cost of international electives to be the primary barriers to participation in global health education. Our results indicated that the development of a rehabilitation global health curriculum available for PM&R trainees throughout the United States may provide an opportunity for trainee development, foster a positive relationship with international partners, and improve the availability of rehabilitation resources for the aging population.